(untitled) (Bangladesh Journal of Animal Science, 2015)
Gayal (Bos frontalis) is a semi domesticated and endangered bovine species in Bangladesh. This study was conducted to know the present distribution, performances and utility of gayal in the home tract. Bandarban Hill district was found the home tract of gayal in Bangladesh. Gayals were reared under extensive management system in the forest of Bandarban Hill district. They browsed forest herbs and grass freely in the forest and came to human dwelling for salt licking. Total number of gayal was counted between 800- 900. The average number of gayal per farmer was 5.01. The coat color of adult gayal was black. White stocking was very prominent in adult gayal. The height at wither and weight for adult males ranged from 126 to 136 cm and 490 to 577 kg, respectively. Reproductive efficiency was high and calving interval was 402 days. They exhibited high disease resistant. The PVC (Pack Cell Volume) and hemoglobin value was 33.5±5.71% and 13.43±2.9 g/dl, respectively. Gayal was used only as meat animal. The high growth rate and reproductive efficiency of gayal in the home tract indicates that this species can be utilized economically if proper breeding plan and sound extension service can be adopted. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23147 Bang. J. Anim. Sci. 2014. 44 (1): 75-84